Barriers to Nurses’participation in Research - Suryani, Maria; Sugiarto, Yogi Dedy; Baskoro, Supri Fajar; Mulyanti, Ucik; Kristiana, Eny; Dominica, Maria; Hadjiman, Hadjiman (Indonesian Journal of Global Health Research, 2024)
The lack nurses participation in research remains a global challenge. The existence of barriers within individual nurses and systems in the workplace can hinder nurses' participation in conducting research. So far there has been no research regarding barriers to nurse involvement in research at the Sint Elisabeth hospital in Semarang. Objective: This study aimed to evaluate barriers to nurse participation in research at Sint Elisabeth hospital Semarang. Method: A descriptive study was conducted involving 384 nurses at Elisabeth hospital Semarang and were selected by convenience sampling. Data was collected using a questionnaire on barriers to nurses' participation in research. Descriptive analysis was carried out in this study. Results: The mean barriers for research participation related to resources and perceived personal relevance of nurses were 3.31 and 2.51 (possible range 1-5), respectively. The highest barrier related to resources is the lack of incentive support or rewards for nurses who conduct research and the lack of financial or other resources to facilitate research activities. The highest barrier regarding perceived personal relevance is the absence of a topic or research idea. Conclusions: Barriers in nurses participation in research related to resources in the hospital were more felt by nurses than barrier related personal relevance.